Analisis Efisiensi Pemasaran Kubis di Kecamatan Kayu Aro Kabupaten Kerinci Provinsi Jambi - Latifa, Dara; Tanjung, Faidil; Sari, Rina (Journal of Agribusiness and Community Empowerment, 2020)
This research is aimed to; 1) describe the marketing system of cabbage, including marketing channels and marketing functions which is done by eachmarketing agencies;2) analyze the structure, conduct, and performance (SCP), marketing margin, farmer's share, and marketing efficiency analysis of cabbage's marketing in Kayu Aro district. The data collection method used in this research was survey. Primary and secondary data were collected and then analyzed using descriptive qualitative method and quantitative method. The findings of this research indicate that; 1) marketing agencies involved in the cabbage marketing structure are farmers, collectors sellers, large sellers, distributor sellers, and retailer sellers. 2) There are four channels of cabbage marketing, and it consists of three channels inside the region and one channel outside the region. 3) Market functions that had been conducted within each marketing channel are exchange function, physic function, and facility function. 4) The market structure analysis of cabbage leads to an oligopoly market. Marketing price is shaped based on a compromise between demand and supply. Furthermore, this study highlighted that marketing channel IV is the most efficient channel for marketing efficiency analysis. Through this study, the writer would like to advise the producers to follow the cabbage marketing structure that had already been formulated, which is marketing channel IV. The local government could create a policy to make marketing efficiency better, for example, by supplying facilities and infrastructure. As for future researchers, there is pressing urgency for further research about marketing efficiency through a market integration approach.